Urinary albumin excretion and progression of renal disease with impaired fibrinolytic activity in type 2 diabetes mellitus - Ebtessam Zakaria; Maha Hossam Al-Din; Nashwa S Ghanem; Noha A Sadik; Maha Assem; Fatma Taha (SpringerOpen, 2015)
Background Diabetic nephropathy is one of the major causes of end-stage renal disease. As impaired fibrinolysis can increase renal fibrosis, we investigated the relationship of impaired fibrinolysis, as assessed by the ratio of plasminogen activator inhibitor-1 (PAI-1) to tissue-type plasminogen activator (t-PA) with urinary albumin excretion (UAE) and renal disease progression in type 2 diabetes. Patients and methods A total of 50 patients with type 2 diabetes and 10 healthy control individuals were included in the study. Participants were subdivided according to UAE. Group 1 (G1) represented control individuals. Group 2 (G2) included patients without albuminuria. Group 3 (G3) included patients with microalbuminuria. Group 4 (G4) included patients with macroalbuminuria. Creatinine clearance and UAE were calculated. PAI-1 and t-PA were measured using an enzyme-linked immunosorbent assay kit, and the PAI-1/t-PA ratio was calculated as an index of impaired fibrinolysis. Results PAI-1 was highly elevated significantly in G4 when compared with the other groups, with a mean of 87.40 ± 17.03 IU/ml against 28.00 ± 6.98 IU/ml in G1, 46.4 ± 7.99 IU/ml in G2, and 64.10 ± 18.26 IU/ml in G3 (P < 0.001). Also, the serum level of t-PA in G4 was highly elevated significantly when compared with G1 and G2 with means of 16.85 ± 5.63 IU/ml against 7.95 ± 1.91 IU/ml and 10.45 ± 2.63 IU/ml, respectively (P < 0.001). The ratio of PAI-1/t-PA in G4 was significantly higher when compared with G1 (mean of 5.94 ± 2.81 against 3.54 ± 0.43; P = 0.01). PAI-1 and t-PA showed a significant positive correlation with UAE. Receiver operating characteristics curve analysis revealed that only PAI-1 and t-PA were significant discriminated factors for microalbuminuria and macroalbuminuria (P < 0.001). Conclusion Serum levels of PAI-1 and t-PA and the PAI-1/t-PA ratio were significantly increased in diabetic patients with higher UAE. Impaired fibrinolysis and increased UAE were associated with renal disease progression.